Preparation method of melamine adhesive with long storage period

By adjusting the key factors in the preparation process, melamine glue with long shelf life and low formaldehyde emission was prepared, which solved the problems of short shelf life and high formaldehyde emission, achieving wider application and higher environmental protection performance.

CN119552609APending Publication Date: 2025-03-04DEHUA TB NEW DECORATION MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411608368.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The short shelf life, poor initial viscosity, insufficient water resistance and high formaldehyde emission limits its application in actual production.

Method used

Melamine gels with long shelf life and low free formaldehyde content were prepared by adjusting the molar ratio of formaldehyde, adding urea in stages, introducing protective colloids and alcohol solutions, and adding oxidants and stabilizers after the preparation process.

Benefits of technology

It significantly extends the shelf life of melamine glue, improves its stability and heat resistance, reduces formaldehyde emission, meets environmental protection requirements, and expands its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of melamine adhesives, and discloses a melamine adhesive with a long storage period and a preparation method thereof. On the basis of the melamine adhesive, the oxidation mixing agent, the alcohol solution and the stabilizer are introduced, so that the storage stability of the adhesive is improved, the storage time of the melamine adhesive is prolonged, and the formaldehyde emission is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of adhesives, and in particular to a method for preparing melamine glue with a long storage period. Background Art

[0002] Melamine glue is an important thermosetting resin with wide commercial application value and is one of the thermosetting resins with the largest output in the world. However, it has the disadvantages of short storage period, poor initial adhesion, insufficient water resistance and high formaldehyde emission, which seriously limit the application of melamine glue in actual production.

[0003] The hydroxymethyl urea of ​​melamine glue forms primary micelles through intermolecular interactions, and the primary micelles further aggregate and polycondense to form metastable colloidal particles. The dehydration condensation of -CH2OH in the colloid causes the colloid to solidify, and the free formaldehyde in the colloid will also accelerate the resin polycondensation process. In addition, the colloidal particles themselves are prone to agglomeration and precipitation during storage. The storage time of melamine glue can only be maintained for about 15 days, which seriously limits the transportation radius and application field of melamine glue.

[0004] At present, in order to address the problem of poor storage stability of melamine glue, scientific research and actual production mainly adopt methods such as controlling the degree of cross-linking of the resin in the urea-formaldehyde condensation process, such as increasing the formaldehyde / urea molar ratio, adding inhibitors, macromolecular protective colloids, spray drying, or after the urea-formaldehyde condensation to form the resin, using hydroxymethyl end-capping or adding inorganic fillers to extend the storage life of the resin.

[0005] The reaction between formaldehyde and urea is a reversible reaction. The greater the molar ratio of formaldehyde / urea, the better the initial viscosity of the resin and the more stable the resin. However, the higher the formaldehyde content, the more free formaldehyde there is, the greater the harm to the human body, and it is not in line with my country's green development concept. Adding inhibitors and protective colloids in the preparation process can control the degree of crosslinking, but it will also affect the primary viscosity of the adhesive. The spray drying method converts metastable colloidal particles into resin powder, eliminating the aggregation and precipitation problem of colloidal particles, but the energy consumption of spray drying is too high, and toxic formaldehyde is released during the process, polluting the environment.

[0006] However, in the research on the storage stability of resin, there are few studies on efficient, safe, low-energy and environmentally friendly stabilizers. Therefore, from the perspective of economic feasibility and green sustainable development, improving the storage stability of resin has important research significance. Summary of the invention

[0007] The purpose of the present invention is to solve the problem of short storage period of melamine glue synthesized by traditional methods, and to provide a preparation method of melamine glue with long storage period. The melamine glue provided by the present invention has a long storage period and a low free formaldehyde content.

[0008] The present invention is achieved through the following technical solution, comprising the following steps: S1. Place 250-300 parts of formaldehyde solution, 1-5 parts of polyvinyl alcohol, 50-100 parts of urea, and 20-30 parts of aqueous solution into a reaction vessel, turn on a stirring device, and adjust the pH to 8.0-9.0 with an alkali solution; The concentration of the formaldehyde solution is 36% to 39%; the alkali solution is at least one of a sodium hydroxide solution, a potassium hydroxide solution, a calcium hydroxide solution and a triethanolamine solution, and the concentration is 20% to 40%; S2, turning on the heating device to carry out a hydroxymethylation reaction (addition reaction) at a temperature of 85°C to 95°C; In this stage, depending on the F / U molar ratio, the reaction will produce mono-, di-, and tri-hydroxymethyl urea; the addition reaction equations of mono- and di-hydroxymethyl urea are as follows: H2NCONH2+CH2O→H2NCONHCH2OH (monomethylol urea) H2NCONH2+2CH2O→HOCH2HNCONHCH2OH (dihydroxymethyl urea) In aqueous solution, the first stage addition reaction of melamine adhesive is reversible, and the reaction will continue until equilibrium is established; S3. At a temperature of 85℃~90℃, adjust the pH to 3.8~5.1 with acid solution to carry out polycondensation reaction; the product is also polycondensed into formaldehyde resin. The overall reaction equation is: nH2NCONH2+nHCHO→H[NHCONHCH2]OH+(n-1)H2O The acid solution is at least one of formic acid solution, ammonium sulfate solution, hydrochloric acid solution and citric acid solution, with a concentration of 10-40%; S4. At a temperature of 85°C to 95°C, adjust the pH to 8.0 to 9.5 with alkaline solution, add 5 to 10 parts of urea and 50 to 150 parts of melamine, and carry out heat preservation reaction for 45 minutes to 95 minutes; S5, cooling to 70°C-80°C, adding 50-100 parts of urea and 20-50 parts of alcohol solution; Preferably, the alcohol solution is at least one of methanol, ethylene glycol, propylene glycol, butylene glycol, chloroethanol and furfuryl alcohol, with a concentration of 92% to 99%; the alcohol hydroxyl group is a polar group, and the positive and negative charges are unevenly distributed, which will produce a certain repulsive force. In the polycondensation reaction, this repulsive force can hinder the approach and reaction between molecules, thereby controlling the rate and degree of the polycondensation reaction; Preferably, the alcohol solution is a mixture of methanol and ethanol in a mass ratio of 2:1;

[0009] S6, cooling to 30°C to 40°C to obtain the initial long storage period melamine glue; S7, add 1 to 3 parts of oxidizing agent, and carry out free formaldehyde oxidation reaction for 30 minutes to 90 minutes to reduce the active free formaldehyde in the resin and improve stability; Preferably, the oxidant is at least one of sodium dichromate, potassium dichromate, potassium permanganate, hydrogen peroxide, ammonium persulfate, sodium hypochlorite, sodium percarbonate, sodium perborate and potassium perborate; taking hydrogen peroxide as an oxidant, formaldehyde reacts with hydrogen peroxide (H2O2) to form formic acid, thereby generating carbonic acid (H2CO3); the specific reaction equation is as follows: HCHO+H2O2→HCOOH+H2OHCHO+H2O2 HCOOH+H2O→H2CO3+H2O Preferably, the oxidant is a mixture of hydrogen peroxide and sodium hypochlorite in a mass ratio of 1:1;

[0010] S8, cooling the obtained environmentally friendly melamine glue to room temperature, and adding 1 to 5 parts of a stabilizer; The stabilizer is an organosilicon compound, a polyether compound or a mixture thereof; Preferably, the silane coupling agent is mainly methyltrichlorosilane, aminosilane, vinylsilane, epoxysilane, allyltrimethoxysilane, etc.; Preferably, the polyether compound is mainly polyether F38, polyether F68, polyether L62, polyether L64, etc.; Preferably, the stabilizer is a mixture of polyether F38 and epoxy silane in a mass ratio of 2:1;

[0011] S9. Stir the mixture thoroughly to ensure that the stabilizer is evenly dispersed in the resin, and then filter it to remove any tiny particles or impurities that may be present.

[0012] In the prior art, during the adhesive preparation process, an inhibitor is added to react chemically with the -CH2OH group to form a stable chemical bond such as an ether bond. Although this can effectively inhibit the early polymerization reaction, it will also reduce the primary viscosity of the adhesive. Moreover, the presence of these stable groups may affect the subsequent curing process, resulting in difficulty in curing melamine adhesive. In addition, although the use of filler-type inhibitors can prevent intermolecular agglomeration by filling the macromolecular structure of the resin, it is generally difficult to achieve a uniform dispersion of the filler. The presence of solid particles will also have an adverse effect on the curing process and may also lead to inconsistency in the performance of the cured product.

[0013] In the preparation process of the present invention, the method for improving the storage stability of melamine glue is mainly in the following aspects: ① In the preparation process, by increasing the molar proportion of formaldehyde and adding urea in stages, and introducing protective colloids and alcohols, melamine glue with suitable initial viscosity and cross-linking degree is obtained.

[0014] ② Using oxidants to remove free formaldehyde can significantly reduce formaldehyde emissions, alleviate environmental pollution, and enhance the stability of the resin.

[0015] ③ Add silane coupling agent and / or polyether after the preparation process. On the one hand, the polar end of the silane coupling agent forms hydrogen bonds with -CH2OH and formaldehyde, preventing formaldehyde from continuing to condense; on the other hand, the dispersing effect of the polyether and the steric hindrance effect brought about by the long chain structure further inhibit the occurrence of the condensation reaction.

[0016] ④ The combination of silane coupling agent and polyether, through the good compatibility of the non-polar end of the silane coupling agent and the polyether, jointly constructs a long-chain structure containing multiple polar functional groups. These polar groups can form hydrogen bonds with -CH2OH groups and formaldehyde molecules, and the long-chain structure can fold to form a complex spatial conformation, and then embed into the melamine glue network. This unique structure effectively isolates the -CH2OH groups and formaldehyde molecules that may continue to participate in the condensation reaction, significantly inhibits unnecessary side reactions, optimizes the microstructure of the resin, and improves the overall performance of the material.

[0017] ⑤ The bond energy of hydrogen bonds is low. During the subsequent heating and curing, the hydrogen bonds will be broken, and the binding effect of hydrogen bonds on -CH2OH and formaldehyde will disappear, which will not affect the curing speed and final performance of the resin.

[0018] ⑥ During heat curing, the hydroxyl groups in the silane coupling agent and polyether, -CH2OH in the melamine glue, and formaldehyde condensation can all condense to increase the crosslinking degree of the resin. Through this efficient crosslinking between multiple components, the heat resistance, mechanical strength and chemical stability of the final product can be significantly improved.

[0019] The present invention adopts a combination of physics and chemistry to modify the resin, regulates the molar ratio of formaldehyde, adds an alcohol solution and an oxidant in the preparation process, and adds a stabilizer in the later stage of the preparation process. The stabilizer is a mixture of a polyether and a silane coupling agent. While not affecting the curing efficiency, the storage period and stability of the melamine glue are improved, and the free formaldehyde content is reduced. The challenge faced by the prior art in improving the crosslinking degree by adjusting the preparation process is overcome, that is, while achieving a higher crosslinking degree, if the initial viscosity is too high, further curing is likely to occur during storage. On the contrary, if the initial viscosity is too low, the bonding performance of the colloid will be affected.

[0020] (1) The storage period of melamine glue was significantly extended from the initial 15 days to 40 days, thereby expanding its application range in the market and solving the market limitation problem caused by the short storage period.

[0021] (2) By introducing oxidizing agents, alcohol solutions and stabilizers, the storage stability of the adhesive is improved, the risk of curing and deterioration is reduced, and the stable performance of the product during long-term storage is ensured.

[0022] (3) The formaldehyde emission was reduced from 0.29 mg / L to 0.15 mg / L, which met the environmental protection requirements, reduced the potential harm to the environment and human health, and was in line with the current trend of green development. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0024] Example 1: Colloid Shelf Life Determination S1. Place 300 parts of formaldehyde solution, 5 parts of polyvinyl alcohol, 100 parts of urea and 30 parts of aqueous solution into a reaction vessel, start a stirring device, and adjust the pH to 8.0 with an alkali solution; The concentration of formaldehyde solution is 39%; the alkali solution is sodium hydroxide solution with a concentration of 40%; S2, turning on the heating device, and carrying out a hydroxymethylation reaction (addition reaction) at a temperature of 95°C; S3, at 90℃, adjust pH to 3.8 with acid solution to carry out polycondensation reaction; the product is also polycondensed into formaldehyde resin; the acid solution is formic acid solution with a concentration of 40%; S4, at 95°C, adjust the pH to 9.0 with alkaline solution, add 10 parts of urea and 150 parts of melamine, and carry out heat preservation reaction for 90 minutes; S5, cooling to 80°C, adding 100 parts of urea and 30 parts of alcohol solution; The alcohol solution is a mixture of methanol and ethylene glycol (mass ratio is 2:1) with a concentration of 92% to 99%; S6, cooling to 30°C to obtain the initial long storage period melamine glue; S7, adding 2 parts of an oxidizing agent, and carrying out a free formaldehyde oxidation reaction for 60 minutes to reduce the active free formaldehyde in the resin and improve stability; the oxidizing agent is a mixture of hydrogen peroxide and sodium hypochlorite, and the mass ratio of hydrogen peroxide to sodium hypochlorite is 1:1; S8, cooling the obtained environmentally friendly melamine glue to room temperature, and adding 4 parts of a stabilizer; The stabilizer is a mixture of polyether F38 and epoxy silane, and the mass ratio of polyether F38 to epoxy silane is 1:1; S9. Stir the mixture thoroughly to ensure that the stabilizer is evenly dispersed in the resin, and then filter it to remove any tiny particles or impurities that may exist; The storage period of the resin prepared above was measured according to the method of GB / T 7123-2002 "Determination of trial period and storage period of adhesives", and the result showed that the storage period of the colloid at room temperature was 40 days.

[0025] Comparative Example 1: Effect of Alcohols on Storage Period The difference from Example 1 is that in step S5, different alcohol solutions are added respectively, and the control group is a group without adding alcohol. The alcohol substances are methanol; ethylene glycol; propylene glycol; butylene glycol; furfuryl alcohol; chloroethanol; methanol + ethylene glycol, and the addition amount is 30 parts. According to the method of GB / T 7123-2002 "Determination of the trial period and storage period of adhesives", the storage period of the above 8 groups of melamine adhesives made with different alcohol substances and without adding alcohol is measured. The storage period of the colloid under different alcohol addition treatments is shown in Table 1.

[0026] Table 1 Determination of storage period

[0027] Comparative Example 2: Effect of oxidants on formaldehyde release The difference from Example 1 is that: in the step S7, different oxidants are added respectively, and a control group is formed without adding an oxidant, and the types of oxidants are hydrogen peroxide; sodium hypochlorite; sodium percarbonate; ammonium persulfate; hydrogen peroxide + sodium hypochlorite (mass ratio is 1:1); the remaining components and preparation process are the same as those in Example 1; The formaldehyde emission of the melamine adhesive samples prepared using different oxidants was also measured; the formaldehyde emission was tested in accordance with GBT 17657-2013 "Physical and Chemical Properties Tests for Artificial Boards and Faced Artificial Boards" (dryer method); the test results are shown in Table 2.

[0028] Table 2 Formaldehyde emission tracking

[0029] Comparative Example 3: Effect of stabilizer on storage period The difference from Example 1 is that: in the step S8, different stabilizers are added respectively, and a control group is taken without adding stabilizer, and the stabilizer categories are polyether F38; polyether F68; polyether L64; polyether L62; methyltrichlorosilane; aminosilane; vinyl silane; epoxy silane; allyltrimethoxysilane; polyether F38 and epoxy silane (mass ratio is 1:1), polyether F38 and allyltrimethoxysilane (mass ratio is 1:1), polyether F38 and vinyl silane (mass ratio is 1:1), polyether L64 and epoxy silane (mass ratio is 1:1), and the remaining components and preparation process are the same as those in Example 1; Referring to GB / T14074-2017 “Test methods for adhesives and resins for wood industry”, the time when the colloid begins to precipitate after adding different polyether compounds was tested. The results are shown in Table 3.

[0030] Table 3 Stabilizer effect determination

[0031] The condensation reaction of urea and formaldehyde is a reversible reaction. There are unreacted urea, free formaldehyde and active groups such as hydroxymethyl, carboxyl and amino groups in melamine glue, which can continue to condense and produce precipitation. The weak interaction force between particles may also cause some condensation products of urea and formaldehyde (such as monomethylol urea, dimethylol urea, etc.) to aggregate to form larger particles.

[0032] Adding an appropriate amount of silane coupling agent to melamine glue can slow down the formation of precipitation during storage. The alkoxy groups in the silane coupling agent are hydrolyzed to produce silanols, which can form hydrogen bonds with the hydroxyl and methylol groups in the melamine glue, reducing the activity of the active groups in the melamine glue and forming a more stable three-dimensional network structure to prevent small molecules from precipitating from the solution, thereby reducing precipitation during storage.

[0033] A small amount of functional groups (such as hydroxyl) in polyether can also form hydrogen bonds with active functional groups (such as amino, methylol, etc.) in melamine glue, reducing the activity of active groups in melamine glue and reducing the generation of precipitation. Long-chain polyethers can adsorb melamine glue particles, and they will form a physical barrier on the surface of the particles. This barrier increases the distance between particles and reduces the chance of direct contact between particles, thereby inhibiting the aggregation and precipitation of particles. Polyether molecules occupy a large space volume in the solution and have a steric hindrance effect, which can effectively prevent the interaction between solid particles, thereby preventing the aggregation of particles. Polyether has a large molecular size and a slow expansion rate in the resin, and can play its role for a longer time.

[0034] In the melamine glue system, the hydroxyl groups, amino groups, etc. in the polyether and silane coupling agent can form hydrogen bonds with the active groups in the melamine glue to prevent the active groups from condensing to form solid precipitation. The long-chain polyether can provide a steric hindrance effect, which can disperse the free small molecule components and silane coupling agents in the melamine glue, thereby further preventing the active groups from condensing. This steric hindrance helps to maintain the fluidity of the system, prevent excessive condensation, and make the final product more uniform and stable. That is, the polyether and the silane coupling agent have a synergistic effect to form a long-chain structure with multiple dispersed active sites that can form hydrogen bonds. This structure can prevent excessive condensation and can also disperse the colloidal particles, further improving the stability of the colloid.

[0035] Comparative Example 4: Effect of silane coupling agent on adhesive impregnation and peeling performance S1. Making adhesive; The difference from Example 1 is that: in the step S8, stabilizers of different silicon compounds are added respectively, and a control group without adding silicon compounds is used, and the stabilizers are methyltrichlorosilane, aminosilane, vinylsilane, epoxysilane, and allyltrimethoxysilane respectively; the remaining components and preparation process are the same as those in Example 1; S2, making plywood; Prepare a 5-layer artificial board as follows: Use the prepared adhesive to apply glue on both sides of the single board, and set the glue application amount to 380g / m 2 Then, the plates are arranged according to the normal production process requirements. After the arrangement is completed, they are aged for 50 minutes. After the time is up, they are sent to the cold press for pre-pressing. After the pre-pressing, hot pressing is carried out. After the hot pressing is completed, the samples are taken after cooling for 24 hours. S3, immersion stripping performance; Ten specimens were taken from one board and tested for immersion and peeling performance of Class I plywood according to the standard requirements of GB / T 17657-2013 “Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels” (boiling in boiling water for 4 hours, baking at (63±3)℃ for 20 hours, boiling in boiling water for 4 hours, and baking at (63±3)℃ for 3 hours). The test results are shown in Table 4.

[0036] Table 4 Qualified rate determination

[0037] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing melamine glue with a long shelf life, comprising the following steps: S1. Place 250-300 parts of formaldehyde solution, 1-5 parts of polyvinyl alcohol, 50-100 parts of urea, and 20-30 parts of aqueous solution into a reaction container, stir, and adjust the pH to 8.0-9.0 with alkali solution; heat at 85°C-95°C to carry out hydroxymethylation reaction; S2, adjusting the pH to 3.8-5.1 with acid solution to carry out polycondensation reaction; S3, adjusting the pH to 8.0-9.5 with alkaline solution, adding 5-10 parts of urea and 50-150 parts of melamine, and carrying out heat preservation reaction for 45 minutes to 95 minutes; S4, cooling to 70°C-80°C, adding 50-100 parts of urea and 20-50 parts of alcohol solution; S5, cooling to 30°C to 40°C to obtain the initial long storage period melamine glue; S6, adding 1 to 3 parts of an oxidizing agent to carry out an oxidation reaction of free formaldehyde for 30 minutes to 90 minutes; S7. Cool the obtained environmentally friendly melamine glue to room temperature, and add 1 to 5 parts of a stabilizer.

2. The preparation method according to claim 1, characterized in that: The concentration of alkali solution is 20% to 40%; the concentration of formaldehyde solution is 36% to 39%; and the concentration of acid solution is 10% to 40%.

3. The preparation method according to claim 1, characterized in that: The alcohol solution in step S4 is at least one of methanol, ethylene glycol, propylene glycol, butylene glycol, chloroethanol and furfuryl alcohol, and the concentration is 92% to 99%.

4. The preparation method according to claim 3, characterized in that: The alcohol solution is a mixture of methanol and ethylene glycol.

5. The preparation method according to claim 1, characterized in that: The oxidant in step S6 is at least one of sodium dichromate, potassium dichromate, potassium permanganate, hydrogen peroxide, ammonium persulfate, sodium hypochlorite, sodium percarbonate, sodium perborate and potassium perborate.

6. The preparation method according to claim 5, characterized in that: The oxidant in step S6 is a mixture of hydrogen peroxide and sodium hypochlorite.

7. The preparation method according to claim 1, characterized in that: The stabilizer in step S7 is at least one of a polyether and a silane coupling agent.

8. The preparation method according to claim 7, wherein the silane coupling agent is at least one of methyltrichlorosilane, aminosilane, vinylsilane, epoxysilane and allyltrimethoxysilane. 9 . The preparation method according to claim 7 , wherein the polyether compound is at least one of polyether F38, polyether F68, polyether L62 and polyether L64.

10. The preparation method according to claim 7, wherein the stabilizer is a mixture of polyether F38 and epoxy silane.